Bisphosphonate-associated osteonecrosis of the jaw in rheumatology: a sistematic review - F. Capsoni (PAGEPress Publications, 2011)
Osteonecrosis of the jaw (ONJ) is a well-known devastating side effect of parenteral bisphosphonate therapy for cancer. Several ONJ cases have been reported in patients taking oral bisphosphonates for osteoporosis or Paget's disease. Even if the number of cases of ONJ in patients taking oral bisphosphonates are still rare compared to the total exposure, rheumatologists treating bone diseases with bisphosphonates must be aware of this new complication, allowing for prevention and early diagnosis. The patients must be informed on the benefit/risk of bisphosphonate therapy and, when necessary and possible, alternative therapy for postmenopausal osteoporosis should be considered. The need for the patient to be dentally fit and to maintain this state forever should be part of the informed consent for bisphosphonate treatment. It is uncommon for rheumatologists to ask about dental problems but this new bisphosphonate- associated complication highlights the need for this to change. In this paper we review the literature available on this newly described bisphosphonate-induced complication with particular emphasis on ONJ cases related to the use of oral bisphosphonates.